The Expression of Autophagy Markers Beclin1 and LC3B in Prostatic Carcinoma: Immunohistochemical Case-Control Study - Nanis Holah; Marwa Serag El-Dien; Shereen Mahmoud (Iranian Society of Pathology, 2022)
Background and Objective: Prostatic carcinoma represents the second most common cancer diagnosed in men worldwide after lung cancer and the fourth common male malignancy in Egypt. Autophagy is a natural process that has both oncogenic and tumor-suppressive activities. This study aims to evaluate the role of Beclin1 and LC3B in prostatic carcinoma.Methods: This retrospective case-control study was conducted on 110 prostate biopsies divided into two groups (55 prostatic carcinoma, 45 pure benign prostatic hyperplasia (BPH), and 10 BPH with adjacent prostatic carcinoma) retrieved from the archive of the Pathology Department, Faculty of Medicine, Menoufia University, in the period between 2017 and 2020. All cases were stained for Beclin1 and LC3B antibodies. Results: There was a highly significant association between higher Beclin1 and LC3B immunoreactivity score and Gleason score (score 8 and 9) (P=0.002 and 0.000, respectively). Moreover, there was a highly significant direct association between Beclin1 and LC3B expression (r=0.52, P=0.000). Also, there was a significant stepwise increase in Beclin1 positivity among the three studied groups starting from BPH to prostatic carcinoma passing through cases of BPH with neighboring tumor (P=0.000).Conclusion: From the results obtained in the present study, autophagy markers Beclin1 and LC3B were upregulated in prostatic carcinoma. Moreover, both were associated with bad prognostic factors. So, it might be necessary to control autophagy flux in prostatic carcinoma. This might be one of the future therapeutic targets for the management of prostatic carcinoma.